"A Second Bible": Liturgy and Interpretation in the Expositions of John Boys. Issue 1 (2nd January 2018) - Quitslund, Beth
Abstract : The Expositions of the English lectionary by preacher and eventual Dean of Canterbury John Boys (1571–1625) represent a Jacobean Calvinist's attempt to defend the Book of Common Prayer against not only puritans and Catholics but also against the tensions between ceremonial order and scriptural preeminence in the Prayer Book itself. Boys's extensive commentaries, in the form of sermons, sermon notes, and especially in a treatise on the "principall Scriptures" embedded in the prayer and communion services, employ a surprising variety of biblical hermeneutics to bolster the claim that the order of the liturgy is itself a form of scripture. He thus rejects the claims of ceremonial adiaphora, insisting that the Church of England's worship has a better claim to apostolic antiquity and scriptural authenticity than that of either Protestant radicals or the Roman Church.